Effect of Body Condition Score Limousine Crossbred Cow on Cattle Oestrus Response Synchronized using PGF2α Single Dose - Muhammad Zainul Hanif; Putri Utami; Aulia Puspita Anugra Yekti; Asri Nurul Huda; Joko Riyanto; Chusnul Hanim; Mashudi Mashudi; Trinil Susilawati (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
One of the strategies to increase the cattle population in Indonesia is the AI (Artificial Insemination) method. The AI program's improvement of reproductive efficiency can use the oestrus synchronization method. The purpose of this study was to evaluate the effect of body weight and body condition score on the oestrus synchronization response with the brand